Rancang Bangun Sistem Informasi Kepegawaian Pada PT Permata Medika Center - Kurniawan, Renaldi Rahmat; Sihotang, Fransiska Prihatini (MDP Student Conference, 2025)
PT Permata Medika Center is a company engaged in the retail trade of goods and pharmaceutical drugs in pharmacies. Based on interviews, it was found that PT Permata Medika Center faces issues in managing employee data due to data redundancy. To address this problem, a solution in the form of a human resources information system was proposed to assist staff in managing employee data. The resulting human resources information system provides various features, including managing new employee recruitment, job vacancies, attendance, employee data, leave, rewards, punishments, divisions, and resignations. This research resulted in a human resources information system that helps make the recruitment and selection of prospective employees more efficient and aligned with the company's needs. Additionally, it facilitates the recapitulation of attendance data and employee administration, making reporting and decision-making easier and faster.